Science learning development for the deaf: A digital literacy-based learning design - Rina Dwi Kurniawati; Asri Wijiastuti; Yuliyati Yuliyati (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2021)
Digital literacy-based learning is needed for deaf students in understanding style and motion topics. Application assisted learning in the form of e-books is specially designed for the deaf with an attractive design, accompanied by visual animations of the application of style and motion in everyday life. Thus, the understanding of the topic obtained is not only through text. But animations of every kind of style and examples. This research aims to develop and determine the feasibility of digital literacy-based learning designs for deaf teenagers. The development method used in this research is the Dick, Carey and Carey development model with nine stages. The results of this research are a digital literacy-based learning design for style and motion topics for deaf adolescents referring to the 2013 curriculum. 80% percentage, topic expert validation shows 83,5% percentage, and 82.25% special education expert validation. So, the development of digital literacy-based learning designs for the deaf meets the feasibility needs.